Website-Based Library Application Design at SMA Negeri 1 Rainis, Talaud Islands Regency - Iden Balango; Eliyah A M Sampetoding; Tommy Wijaya Sagala; Relly Potoboda; Yulita Sirinti Pongtambing (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Along with the development of the world of science and technology (IPTEK) which is increasingly rapidly, especially in computerization and the internet, the development of information technology using computer aids and the internet has increased significantly in all fields. SMA Negeri 1 Rainis is one of the schools that has a library with various types of books that can support the world of education. In addition to book lending activities carried out by the SMA Negeri 1 Rainis library, other activities in the form of processing book data and disseminating information about the library are still conventional. Therefore, providing information to library users is still very difficult. The result of this research is that the library website of SMA Negeri 1 Rainis has the following advantages: it can be accessed from anywhere at any time via the internet, as a medium for delivering information more efficiently. Has a stratified level of access according to its use (user)